Models of Christian social work - Chirugu, Gianina; Petrov, George Daniel (Technium Social Sciences Journal, 2022)
The purpose of this work is to present the forms of manifestation of Romanian Christian social assistance both in Orthodoxy and in Catholicism. Thus were pursued the fulfillment of objectives such as: Identification of theoretical considerations of the term philanthropy, the importance of philanthropy for the Romanian Orthodox Church from ancient times to the present, highlighting the forms of philanthropy in the Catholic Church, multidimensional comparative analysis of the concept of philanthropy in both the romanian and catholic orthodox churches, improvement of the way of involvement, methods and techniques used in the service of neighbor and active involvement in the coordination of church social assistance activities, centered on social activity. The contribution of the present research, carried out on the philanthropic phenomenon of the Church, on the one hand, aims to ascertain the need for specialization and continuous training and, on the other hand, to assess the impact of projects and programs carried out in communities, on the beneficiaries.